Compliance on safety behaviour among the lift maintenance worker / Shahrul Azhar Mustaffa - Shahrul Azhar, Mustaffa (2021)
This study was conducted to probe the effects of certain factors on Compliance of Safety Behaviour among lift maintenance workers as a very few studies has been conducted. The aim of this study was to examine the influence of five (5) independent variable; (1) Job Safety, (2) Co-Worker Safety, (3) Supervisor Safety, (4) Management Safety and (5) Satisfaction on Safety Programs and Strategy on Compliance of Safety Behaviour among lift maintenance workers. This quantitative study used five (5) element of the Work Safety Scale (WSS) to measure perceptions of safety at work. The result will show that compliance with safety behaviour is significantly related job safety, supervisors safety, management safety, and satisfaction on the programs implemented. However, it has been shown that Co-Worker Safety is less significant related to Safety Behaviour. Recommendations and suggestions for future study were illustrated in the discussion. Moreover, a brief proposal had been discussed on how to implement Safety Behaviour among lift maintenance worker.